(untitled) (Fiep Bulletin - online, 2019)
Aims: The fights as a socio-educational phenomenon to be apprehended by individuals in the educational space, onlymakes sense when referenced the multiplicity of forms and meanings that they assume and that give it pedagogical sense. Thus,what is known today as a pedagogical content of physical education called by fights is the result of a sociocultural constructionthat has been changing and incorporating new meanings over time. Methodology: Bibliographic review by subject. They wereused as references, projects and periodicals published between the years of 1982 to 2017. Objective: to approach the themefights from a contemporary debate in the education, extending to the physical education school with regard to some pedagogicaltendencies and theoretical aspects-methodological. Conclusion: It is noted that there is a basic conception that aims to establisha theoretical foundation on the content fights, inserting in its methodological aspects, the development of motor learning that canbe used from the common sense by those who do school physical education.